Analisis Faktor-faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan (Studi Kasus pada Wajib Pajak PBB Desa Jatirejo di Mojokerto) - Sari, Della Nur Lita; Rohayati, Suci (Jurnal Pendidikan Akuntansi (JPAK), 2026)
Land and Building Tax (PBB) is one of the main sources of local government revenue that plays an important role in financing regional development. Although the realization of PBB revenue in Mojokerto Regency has exceeded the targeted amount, this condition does not fully reflect voluntary taxpayer compliance, particularly at the village level. In Jatirejo Village, the high level of PBB realization is still largely influenced by active tax collection mechanisms carried out by village officials. This study aims to analyze the factors influencing taxpayer compliance in paying Land and Building Tax, with a focus on taxpayer understanding, tax penalty sanctions, and taxpayer attitudes in Jatirejo Village, Mojokerto Regency. This research employs a quantitative approach. The sampling technique used was accidental sampling, with data collected through questionnaires distributed to 55 respondents in Jatirejo Village. The data were analyzed using multiple linear regression analysis with IBM SPSS Statistics 27 for Windows. The results of the t-test indicate that taxpayer understanding and tax penalty sanctions partially have a significant effect on taxpayer compliance. Meanwhile, taxpayer attitudes do not have a significant partial effect. The F-test results show that taxpayer understanding, tax penalty sanctions, and taxpayer attitudes simultaneously have a positive and significant effect on the level of Land and Building Tax compliance. The implications of this study suggest that improving PBB compliance in rural areas requires strengthening taxpayer understanding and the consistent enforcement of tax penalty sanctions, rather than relying solely on the development of positive attitudes toward taxation.